EMPOWERMENT OF WOMEN'S GROUP IN ENTREPRENEURIAL DEVELOPMENT IN CURUG SULANJANA VILLAGE: PKM PEMBERDAYAAN KELOMPOK PEREMPUAN DALAM PEMBINAAN KEWIRAUSAHAAN DI DESA CURUG SULANJANA - Pramudi Harsono (Yayasan Education and Social Center, 2021)
The Student Work Lecture (KKM) activities in Community Service (PPM) are required to practice science, technology, art, law, art, and entrepreneurship and indeed expected to be a motivator and facilitator of development efforts, especially in rural areas. Various problems exist, and finding solutions to problems, of course, takes the role and participation of KKM-PPM participants with the local village community where the KKM location is located. The program implemented is expected to be achieved goals and targets through several implementations of program 1). Economic Affairs: Assistance of MSMEs and Cooperatives 2). Religion 3). Socio-cultural and community empowerment 4)Health and legal services. The potential of MSMEs and community empowerment is essential because of the participation of women's community groups because of the potential of MSME economic actors and natural excellence, namely melinjo fruit as the leading commodity of the community in the village of Curug Sulanjana Gunungsari District, Serang Regency, Banten Province. Evaluate in the implementation of this program is carried out simply by recording each activity with the results and monitoring from the government as the organizer of training and mentoring in order to know the extent of product development that will be produced